Secretome from Human Umbilical Cord Mesenchymal Stem Cells Ameliorates Ovarian Aging in a Murine Model - Intan, Yulice Soraya Nur; Soetrisno, Soetrisno; Laqif, Abdurahman; Indarto, Dono; Dirgahayu, Paramasari; Pamungkasari, Eti P.; Putra, Agung (Trends in Sciences, 2026)
Ovarian aging represents a complex biological process characterized by follicular depletion, hormonal dysregulation, and chronic inflammation. We investigated the therapeutic potential of the secretome derived from human umbilical cord mesenchymal stem cells (S-HUMCMSCs) in naturally aged female mice. Administration of S-HUMCMSCs significantly reduced serum FSH levels (from 5.43 ± 1.59 to 3.07 ± 2.69 mIU/mL, p < 0.05), decreased senescent cell percentage (from 27.35 ± 0.82% to 8.37 ± 0.85%, p < 0.001), and modulated inflammatory markers with reduction in TNF-α (from 188.23 ± 83.31 to 4.55 ± 4.78 ng/mL, p < 0.001) and elevation in IL-10 (7.55 ± 7.77 ng/mL, p < 0.05). Additionally, S-HUMCMSCs treatment decreased p53 expression 179.17 ± 170.48 vs. 549.67 ± 243.62 in aged controls, p < 0.025 and preserved ovarian follicular architecture. A comparative analysis with 17β‑estradiol therapy demonstrated comparable efficacy in improving ovarian parameters. Although no formal toxicological or long‑term safety assessments were conducted, no adverse clinical signs or behavioral abnormalities were observed during the study period. These findings establish S-HUMCMSCs as a promising cell-free regenerative approach for managing age-related ovarian dysfunction by modulating multiple pathways involved in senescence, inflammation, and hormonal homeostasis. HIGHLIGHTS Restoration of HPO Axis Homeostasis: Administration of S-HUMCMSC secretome significantly ameliorated age-related hormonal dysregulation, evidenced by the normalization of serum FSH levels in a naturally aged murine model. Attenuation of Cellular Senescence: The intervention demonstrated potent senolytic properties, significantly reducing the percentage of senescent cells and downregulating p53 expression in ovarian tissue. Modulation of the Inflammatory Microenvironment: S-HUMCMSC therapy shifted the systemic cytokine profile towards an anti-inflammatory state, characterized by a significant reduction in TNF-α and upregulation of IL-10. Comparable Efficacy to 17β‑Estradiol: The cell‑free secretome demonstrated therapeutic efficacy comparable to standard hormone replacement therapy (17β‑estradiol) in preserving follicular architecture, without evidence of adverse effects during the study period. GRAPHICAL ABSTRACT